The Role of Resilient Supply Chains in Enhancing Competitiveness and Performance of SMEs: A Case Study in the SMI Sector - Kulsaputro, Januar; Fole, Asrul; Safitri, Khoerun Nisa; Aini, Nurul (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to explore the role of resilient supply chains in improving the competitiveness and performance of micro, small and medium enterprises (MSMEs) in Makassar City. The research method used is a mixed method approach involving 100 respondents from various sectors including food and beverages, handicrafts, and textiles. The results show that 75% of the respondents have implemented elements of resilient supply chains, such as supplier diversification and the use of information technology, which contribute to improved operational efficiency. Regression analysis shows a significant positive relationship between the implementation of resilient supply chains and the competitiveness of MSMEs, with a regression coefficient of 0.65 (p < 0.01). In addition, 70% of the respondents reported an increase in sales and customer satisfaction after adopting resilient supply chain strategies. These findings are consistent with the literature that emphasizes the importance of flexibility and adaptability in supply chains. This study recommends that MSMEs in Makassar City continue to adopt best practices in supply chain management and seek support from the government to create an ecosystem conducive to business growth. The results of this research are expected to contribute significantly to the development of supply chain management theory and practice in the small and medium industrial sector in Indonesia.